2016
DOI: 10.1038/cr.2016.117
|View full text |Cite
|
Sign up to set email alerts
|

Turning rice meiosis into mitosis

Abstract: Introduction of clonal reproduction through seeds (apomixis) in crops has the potential to revolutionize agriculture by allowing self-propagation of any elite variety, in particular F1 hybrids. In the sexual model plant Arabidopsis thaliana synthetic clonal reproduction through seeds can be artificially implemented by (i) combining three mutations to turn meiosis into mitosis (MiMe) and (ii) crossing the obtained clonal gametes with a line expressing modified CENH3 and whose genome is eliminated in the zygote.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 51 publications
2
117
0
1
Order By: Relevance
“…We previously got a Cas9‐derived Ososd1 with a frame‐shifted mutation (a G insertion at the 17 nt of the OsOSD1 sgRNA target sequences shown in Figure A). In this Ososd1 mutant, behaviors of chromosomes were normal during meiosis I, but the process was ended at production of dyads without second meiotic division, similar to the reported Ososd1 allele (Figure P–S) (Mieulet et al ).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…We previously got a Cas9‐derived Ososd1 with a frame‐shifted mutation (a G insertion at the 17 nt of the OsOSD1 sgRNA target sequences shown in Figure A). In this Ososd1 mutant, behaviors of chromosomes were normal during meiosis I, but the process was ended at production of dyads without second meiotic division, similar to the reported Ososd1 allele (Figure P–S) (Mieulet et al ).…”
Section: Resultssupporting
confidence: 86%
“…To alter meiosis into mitosis, we mutated OsSPO11-1, OsREC8, and OsOSD1 these three genes and consequently generated a MiMe phenotype. Unlike the reported OsMiMe line (Mieulet et al 2016), we mutated OsSPO11-1 instead of PAIR1, suggesting that any gene essential for double-strand break formation is sufficient to generate MiMe line in rice. In AOP, we edited OsMATL with target site near C termini of the CDS, similar to the mutant sites previously reported (Yao et al 2018), to generate the clonal progeny through a haploid inducing process.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previously, an important finding was reported that a simultaneous knock‐down of three genes related to meiosis, SPO11‐1 , REC8, and OSD1 , can turn from the process of meiosis of egg cells to that of mitosis (Mitosis instead of Meiosis; MiMe) in Arabidopsis and rice. Namely, this demonstrated that scientists can induce egg cells carrying diploid genomes by an asexual process (Mieulet et al 2016). Further studies revealed that two genes, such as Babyboom1 ( BBM1 ) and Matrilineal ( MATL ), which are involved in parthenogenesis development of egg cells and haploid induction ability, respectively, are important for asexual development of egg cells in maize and rice (Kelliher et al 2017; Khanday et al 2019).…”
mentioning
confidence: 99%
“…Here we show that heterozygosity of F 1 hybrid rice can be fixed and thus propagated without additional crossing. First, we showed that multiplex editing of three key meiotic genes 5,6 in hybrid rice leads to the production of clonal diploid gametes and tetraploid seeds. Next, editing of the MATRILINEAL ( MTL ) gene that involved in fertilization 7,8 results in the induction of haploid seeds in hybrid rice.…”
mentioning
confidence: 99%